Pictogram Design of Objects in The University of National Development “Veteran” of East Java Environment - Widyasari; Sutejo; A. N. Yunisya (Nusantara Science and Technology Proceedings)
Universitas Pembangunan Nasional “Veteran” Jawa Timur (University of National Development “Veteran” of East Java, subsequently referred to as UPN “Veteran” of East Java in this paper) has several signature objects within the perimeter of the university’s environment, such as physical objects (tools, things, places) and non-physical objects (action, activity, information). Those signature objects can be visualized into symbol or pictogram that signify the ideas and simplify the physical shape of the real object. Pictograms can serves as a visual language to communicate a message or information that will be easily understood by the audience. One optimization form for the use of pictogram is as the signage in the implementation of visual communication media in the UPN "Veteran" environment of East Java. The method used in this design is a qualitative method by finding relevant literature, collecting primary and secondary data, analyzing the data using the TOWS Matrix table to determine the Unique Selling Proposition, and analyzing the insight of the target audience to develop creative solutions. From the results of the TOWS Matrix analysis, a Unique Selling Proposition was obtained in the form of grouping pictograms into several groups of objects, namely Vision and Mission of UPN "Veterans" of East Java, UPN "Veterans" of East Java’s Objectives and Strategies, State Defense Values, Faculties and Study Programs in the UPN "Veteran" of East Java, Student Activity Unit in the UPN" Veteran "East Java environment, and Facilities in the UPN "Veteran" of East Java’s environment. While from the results of the target audience's insights analysis, the creative solutions was found through the usage of graphic elements in pictogram designs, namely elements of color and color taken from the distinctive characteristics of UPN "Veteran" East Java.